CONTRASTING THE PERFECT IN ENGLISH AND IN MACEDONIAN (Journal of Contemporary Philology, 2018)
The  paper  presents  the  results  of  the  contrastive  analysis  between  present  perfect simple and present perfect continuous in English, and the perfect in Macedonian in order to determine the similarities and differences between these tenses . The analysis is based on data from various sources, as well as on the data from The Macedonian English Learner Corpus (MELC), which is an electronic database  containing  texts  produced  by  learners  of  the  English  language.  The  results  of  the  contrastive  analysis  provide  new  insights  useful  in  English  language  teaching.  Relying  on  the  assumption  that  the  Macedonian  language  influences the acquisition process of present perfect simple and present perfect continuous, this article points out the typical problems that Macedonian learners are expected to face while studying the two categories under examination.
Keywords: present perfect; Macedonian perfect; contrastive analysis